Evaluation of Generic Fertiliser as an Alternative Inorganic Nitrogen Source for Ethanolic Glucose Fermentation by Saccharomyces cerevisiae: Glucose ethanolic fermentation using generic fertiliser - ASSAN, THRACESY MUNAH; SAHARI, EFFA SHAHRINA; SUHAILI, NURASHIKIN; AWANG ADENI, DAYANG SALWANI; DEVAGI KANAKARAJU; VINCENT, MICKY (Borneo Journal of Resource Science and Technology, 2023)
In the studies and production of bioethanol, the preferred fermenting yeast (Saccharomyces cerevisiae) is usually cultured in liquid broth that contains yeast extract and peptone. However, the use of these laboratory and scientific grade chemicals is costly, making them impractical for mass bioethanol production. Therefore, this study was conducted to evaluate the feasibility of glucose ethanolic fermentation by S. cerevisiae using generic fertiliser formulations to provide inorganic nitrogen, phosphorus, potassium and trace elements (NPK-TE). Fermentation media of different generic fertiliser strength at 0.5X, 1.0X and 2.0X Fertiliser Nitrogen Equivalents (FNE), as compared to the conventional Yeast Extract-Peptone (YEP) medium as control, was used as fermentation broth during the ethanolic fermentation of glucose. Based on the results, S. cerevisiae cultured in YEP broth produced the highest cell concentration for both wet (21.93 g/L) and dry cells (3.87 g/L), with rapid increment observed in the first 72 h of fermentation. By the end of the fermentation period, lactic acid (3.14 g/L) and acetic acid (0.96 g/L) levels were recorded to be the lowest in YEP medium while their concentration (lactic acid, 8.08 g/L) and (acetic acid, 2.67 g/L) were highest in 2.0X FNE fertiliser medium. Results indicated that the best theoretical ethanol yield (TEY) among the fertiliser media was achieved when fermentation was performed in the 0.5X FNE fertiliser medium, with a TEY of 86.18%. TEY yields were 78.68% and 51.54% in broth with 1.0X and 2.0X FNE, respectively. In general, all three fertiliser media supported ethanolic fermentation of glucose, with the 0.5X FNE fertiliser broth showing a yield that is significantly close to the conventional YEP medium, as seen in the statistical analysis. Similarities in other fermentation profiles such as acetic acid, lactic acid, and biomass production, as well as glucose utilisation, between the results from the YEP samples and samples from the fertiliser broths (at 0.5X and 1.0X FNE) have also shown that generic fertiliser has the potential to be used as an alternative medium to replace the conventional YEP to produce ethanol at a lower cost.